2014
DOI: 10.13075/mp.5893.00056
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary ammonium compounds – new occupational hazards

Abstract: StreszczenieCzwartorzędowe związki amoniowe (quaternary ammonium compounds -QACs) należą do organicznych związków jonowych o unikalnych właściwościach surfaktantów i środków odkażających. Coraz szersze zastosowanie QACs w środowisku pracy, a także poza nim, niesie ze sobą nowe zagrożenia zdrowotne dla osób eksponowanych i służby medycyny pracy. W artykule przedstawiono wyniki przeglądu piśmiennictwa na temat wpływu amin czwartorzędowych na organizm człowieka. QACs mogą działać drażniąco na skórę i błony śluzow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
(37 reference statements)
0
9
0
1
Order By: Relevance
“…Because of antimicrobial properties of quaternary ammonium compounds, they are used in the food and medical industries for surfaces, appliances and tools of cleaning. These materials have a variety of industrial and consumer applications, including use in drilling muds, fabric softeners, hair conditioners, emulsifying agents and sanitizers/disinfectants [22,23]. It has been determined that the microbiological effect on paper is about 1% of aqueous solutions of quaternary ammonium compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of antimicrobial properties of quaternary ammonium compounds, they are used in the food and medical industries for surfaces, appliances and tools of cleaning. These materials have a variety of industrial and consumer applications, including use in drilling muds, fabric softeners, hair conditioners, emulsifying agents and sanitizers/disinfectants [22,23]. It has been determined that the microbiological effect on paper is about 1% of aqueous solutions of quaternary ammonium compounds.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that the balance of quaternary ammonium compounds on paper (up to 400 ppm) did not have a significant effect on paper aging processes [24]. Also, quaternary ammonium compounds are used as chemical corrosion inhibitors, plasticisers for textile and paper production and anti-static agents for cellulose fibers [22,25].…”
Section: Introductionmentioning
confidence: 99%
“…Compounds having 12-14 carbon atoms in the aliphatic chain show the highest surface activity. In turn, negatively charged chlorine ions increase the biocidal activity (Obłąk & Gamian, 2010;Lipińska-Ojrzanowska & Walasiuk-Skorupa, 2014). Due to the broad spectrum of activity and high thermal stability, among others, QACs are used as active ingredients in biocides.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that QACs are more efficient against Grampositive than Gram-negative bacteria. When QACs are used as disinfectants, the concentration applied is almost always below 1000 ppm (Tezel & Pavlostathis, 2011;Lipińska-Ojrzanowska & Walasiuk-Skorupa, 2014). They are used in medicine and many industries (food, cosmetics, paper) as biocides and even drugs (Raghavendra, 2002;Xiao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation